Pengaruh Latihan Fisik terhadap Penurunan Kadar Gula Darah pada Pasien Diabetes Melitus Tipe 2 - Yani Trihandayani; Tri Oktovian; Seftiyani Seftiyani; Nazwa Niyatujahro; Sekar Tri Andini; Muhammad Faisal Ghani (PPNI UNIMMAN, 2025)
Diabetes Mellitus (DM), known as diabetes, is a group of metabolic disorders characterized by an increase in blood glucose levels or hyperglycemia (Ike Prafita & Masnif 2020). The purpose of this literature review is to evaluate the effect of physical activity on reducing blood sugar levels in patients with type 2 diabetes mellitus. The literature search method uses the google scholar database and hurzing publish or perish (2020-2024) using the keywords “Diabetes Mellitus” AND “Physical Exercise” AND “Blood Glucose Level Decrease”. There were 5 journals that fit the inclusion criteria set. The results of the literature analysis found were published in 2020, 2021, and 2022, the research design used was pre-experimental. The sampling technique used was purposive sampling, easy touch, hypothesis. The research instrument used was an observation sheet, the data analysis used was mostly 80% paried sample T test. The results of the review of all journals show that physical exercises such as walking, diabetic gymnastics, and aerobics can significantly reduce blood glucose levels before and after the most effective is the activity of walking providing the greatest reduction compared to other types of exercise. Health workers can apply the effect of physical exercise in the form of walking in reducing blood sugar levels in patients with type 2 diabetes mellitus.